2019
DOI: 10.1021/acsomega.9b00192
|View full text |Cite
|
Sign up to set email alerts
|

Conformational and Stereodynamic Behavior of Five- to Seven-Membered 1-Aryl-2-iminoazacycloalkanes

Abstract: The stereodynamic behavior of 1-arylpyrrolidin-2-imines, having a C aryl –N stereogenic axis, has been studied by means of dynamic nuclear magnetic resonance and density functional theory calculations, evaluating the steric effect of ortho -aryl substituents. The rotational barrier due to E / Z isomerism about the −C=N–H bond was also determined. The dynamic stereochemistry of homologous six- and seven-membered iminoaza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Since then, steric congestion along with strain effects have been claimed to be the driving force of a wide variety of phenomena ranging from classic textbook examples of reactivity [8][9][10] to state-of-the-art developments in supra-molecular chemistry. [11][12][13] Some phenomena where SH has been invoked to play a major role include: the origin of the rotational barriers of alkanes and other derivatives, [14][15][16][17] the stability of conformers of cycloalkanes and macrocycles, [18,19] the ligand ability towards metal centers, [20,21] the trends in the reactivity of nucleophilic substitution and elimination reactions, [22,23] the torsional barriers of biphenyls and their optically active derivatives, [24] the reactions between tertiary amines and boron derivatives, [25] the geometrical features of methyl like radicals, [26] the stability of cis-trans isomers, [27] the competition between the basicity and nucleophilicity of nucleophiles and the stereopreference and the selectivity of the active site of enzymes or organic catalysts, [28] among others.…”
Section: Introduction Chemical Intuition and Steric Hindrancementioning
confidence: 99%
“…Since then, steric congestion along with strain effects have been claimed to be the driving force of a wide variety of phenomena ranging from classic textbook examples of reactivity [8][9][10] to state-of-the-art developments in supra-molecular chemistry. [11][12][13] Some phenomena where SH has been invoked to play a major role include: the origin of the rotational barriers of alkanes and other derivatives, [14][15][16][17] the stability of conformers of cycloalkanes and macrocycles, [18,19] the ligand ability towards metal centers, [20,21] the trends in the reactivity of nucleophilic substitution and elimination reactions, [22,23] the torsional barriers of biphenyls and their optically active derivatives, [24] the reactions between tertiary amines and boron derivatives, [25] the geometrical features of methyl like radicals, [26] the stability of cis-trans isomers, [27] the competition between the basicity and nucleophilicity of nucleophiles and the stereopreference and the selectivity of the active site of enzymes or organic catalysts, [28] among others.…”
Section: Introduction Chemical Intuition and Steric Hindrancementioning
confidence: 99%
“…A subsequent study where 1‐aryl‐2‐iminoazacycloalkanes were used as the chemical scaffold confirmed this trend …”
Section: Steric Factorsmentioning
confidence: 71%
“…Interestingly, NMR‐spectroscopic observations provided evidence that the novel BODIPY Ugi adducts participate in dynamic conformational processes that were deemed to deserve further attention, especially in view of several recent conformational studies with related aniline‐derived compounds [23–25] . Interestingly, a series of Ugi adducts reported previously by our research group did not show this dynamic effect [21] .…”
Section: Introductionmentioning
confidence: 80%